Experiential avoidance in adolescents with borderline personality disorder: comparison with a non-BPD psychiatric group and healthy controls. Issue 3 (3rd May 2020) - Jones, Jenna; Penner, Francesca; Schramm, Andrew T.; Sharp, Carla
ABSTRACT: Previous research has identified experiential avoidance (EA) as related to a host of adolescent internalizing and externalizing problems, as well as borderline personality disorder, suggesting that it is a crosscutting factor for adolescent psychopathology. It remains unclear whether EA differs among adolescents with BPD compared to adolescents with other psychiatric disorders and healthy adolescents. The aims of this study were to 1) examine EA in adolescents with BPD compared to non-BPD inpatient adolescents and healthy adolescents, and 2) to evaluate whether EA has a unique relationship to borderline pathology over and above internalizing and externalizing. Self-report measures of BPD features, EA, and psychopathology were completed by 692 adolescents (64.5% female, Mage = 15.20). This sample included a group of psychiatric inpatient youth ( n  = 197 BPD; n  = 403 non-BPD) and a group of healthy adolescents ( n  = 92). Results revealed that EA differed significantly across all three groups, with the highest level of EA evidenced in adolescents who had BPD. Furthermore, there was a significant, unique association between BPD symptoms and EA over afnd above internalizing and externalizing pathology. These findings pinpoint EA as an important risk marker and possible target of prevention or intervention for adolescent BPD.